Efektivitas Ekstrak Buah Merah (Pandanus conoideus De Vriese) Asal Kabupaten Poso Sebagai Alternatif Penurun Kadar Gula Darah - Diah, Anang Wahid M. D.; Diani, Ni Kadek Ana; Jura, Minarni Rama (Universitas Tadulako, 2016)
Bioactive compounds contained in red fruit (pandanus conoideus De Vriese) among others are flavonoids and tannins. The compounds are classified as very powerful antioxidants and can inhibit free radicals. This study aimed to determine the effective concentration of the red fruit extract from Poso as an alternative for lowering blood sugar levels. The separatin method used was boiling. The animals test were 15 male of mice (Mmus musculus) induced by ethylene diamine tetra acetic (EDTA). The mice were divided randomly into 5 groups with different treatments. The first, the second, and the third treatments were given red fruit extract each with a concentration of 10%, 20% and 30%. The fourth treatment was given glibenclamide suspension as a positive control, and the fifth treatments was given Na-CMC as a negative control. Data were analyzed using a statistical analysis of variance (Anova) test followed by Duncan test. The results showed that the preclinical test of red fruit extract reduced blood sugar levels of mice, and the most effective concentration was 20% as much as 68% (w/v) with significance level a = 0.05.